KONDISI EKOSISTEM TERUMBU KARANG DI ROTE TIMUR, KABUPATEN ROTE NDAO, TAMAN NASIONAL PERAIRAN LAUT SAWU MENGGUNAKAN METODE MANTA TOW - Achmad, Andy; Munasik, Munasik; Wijayanti, Diah Permata (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Waters of the Savu Sea serves strategic means for the development of East Nusa Tenggara province, because most of the district / city in the province is highly dependent on the Savu Sea. The purpose of this study was to determine the condition of coral reef ecosystems using the Manta Tow in the waters of the East Rote, District of Rote Ndao, province of East Nusa Tenggara in the plan of conservation areas Savu Sea Marine National Park. The results show the percentage of hard coral life cover in the East Rote 3 study sites in the category of bad. The west side has average cover of 23.98%. Mulut Seribu Strait have hard coral life cover percentage of 15.8% and eastern side has the lowest percentage to hard coral life cover average by 12.33%.